The Role of Public Leadership of a Bumdes Director Based on Islamic Values in the Framework of Improving the Local Economy - Siti Komara (Eduvest - Journal of Universal Studies, 2026)
Arya Kemuning is an example of a Badan Usaha Milik Desa (BUMDes) that has successfully generated profits and provided benefits to the surrounding community. This success cannot be separated from the role of the BUMDes director, who has effectively led BUMDes Arya Kemuning in achieving its current performance. This study aimed to analyze the role of public leadership in the management of BUMDes Arya Kemuning, examine the implementation of Islamic values in BUMDes management, and integrate public leadership and Islamic values to enhance the contribution of BUMDes to the local economy. This research employed a qualitative approach, with data collected through interviews and observations. Data analysis was conducted using the Miles and Huberman model, while data validity was ensured through triangulation. The BUMDes director successfully implemented Montgomery Van Wart’s public leadership dimensions, including inspirational integrity, technical-managerial capabilities, and transformational leadership, which were synergized with Islamic leadership values, namely sidiq (truthfulness), amanah (trustworthiness), tabligh (effective communication), and fathonah (competence and wisdom). The results showed that the synergy between Montgomery Van Wart’s public leadership framework and Islamic leadership values effectively contributed to improving the local economy, including through local employment creation and increased village community welfare supported by local revenue (Pendapatan Asli Desa/PAD) and Corporate Social Responsibility (CSR) funds. The integration of professional managerial capabilities with Islamic values became a key factor in the success of BUMDes Arya Kemuning in achieving economic independence while generating positive social impacts for the community.